Blurred in translation: The influence of subjectivities and positionalities on the translation of health equity and inclusion policy initiatives in Aotearoa New Zealand. (November 2021) - Lee, Sandy; Collins, Francis L.; Simon-Kumar, Rachel
Abstract: Growing health inequities among the increasingly diverse population in Aotearoa New Zealand have prompted responses in the healthcare system. Diversity-related policies and programmes have been developed in some District Health Boards (DHB) to address the issues. The translation of such policy into practice is, however, convoluted by subjective interests and power differentials and thus the outcomes of policies may deviate from their original objectives. In this paper we examine how staff in one DHB translate and implement health equity and diversity initiatives in their everyday practices in hospital settings. In high-level institutional thinking, Māori health equity policy is dictated by the Treaty of Waitangi which sets it apart from the cultural competence focus of programmes for other ethnic groups. Drawing on interviews with clinical staff in the DHB, we reveal how intersecting subject positions, including personal histories and institutional roles, influence the interpretation and enactment of these policies and programmes in ways that blur their distinct agendas. As a result, the paper demonstrates how the politics that underpin agendas that distinctly address equity and diversity, as well as the potential for change in these areas, can be compromised in everyday practice on the hospital floor. Highlights: Health equity policy programmes distinct for Māori and culturally diverse groups. Distinct agendas are blurred as clinical staff translate them into practice. Intersection of personal subjectivities and positionalities influence translations. Blurring of agendas in everyday practice compromise potential for change.